2017
DOI: 10.1080/24740527.2017.1374820
|View full text |Cite
|
Sign up to set email alerts
|

A paradigm change to inform fibromyalgia research priorities by engaging patients and health care professionals

Abstract: Background: Research objectives should be focused toward advancing knowledge that has meaningful impact on health. However, research agendas are mostly driven by the health care community, with limited input from patients. Aims: In this study, prioirities of uncertainties for the management of fibromyalgia (FM) that could propel future research were identified by a defined process using the James Lind Alliance Priority Setting Partnership (JLA-PSP) methodology. Methods: As a first step, a survey was distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…The JLA provides a rigorous and transparent five‐step procedure for developing a Priority Setting Partnership (PSP). To date, over 100 PSPs have been conducted around the world, including recent Canadian PSPs on fibromyalgia, kidney cancer, and dementia (Bethell et al, ; Fitzcharles et al, ; Jones et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The JLA provides a rigorous and transparent five‐step procedure for developing a Priority Setting Partnership (PSP). To date, over 100 PSPs have been conducted around the world, including recent Canadian PSPs on fibromyalgia, kidney cancer, and dementia (Bethell et al, ; Fitzcharles et al, ; Jones et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…There were 550 responders to the survey but in only 73% of cases could they be identified as either "patient" or "clinician." Thirteen responders were identified as "organization members," another 14 were labeled as "caregivers," and in 122 responders there was "no identification" (Table 2 in Fitzcharles et al 3 ). It appears, nevertheless, that even responses from the latter three groups were considered in subsequent analyses.…”
Section: Missing Data and Uneven Representation In The Responder Groupmentioning
confidence: 99%
“…Ten priorities for research were eventually identified (Table 4 in Fitzcharles et al 3 ). Each of these is briefly labeled as a source of uncertainty and several questions are cited for clarification under the heading of "sample narrative."…”
Section: The Finalistsmentioning
confidence: 99%
See 2 more Smart Citations